The clinical characteristics and pathogenic variants of primary pigmented nodular adrenocortical disease in 210 patients: a systematic review - Sun, Julian; Ding, Lin; He, Liping; Fu, Hang; Li, Rui; Feng, Jing; Dong, Jianjun; Liao, Lin (Frontiers in Endocrinology, 2024)
Aims: Primary pigmented nodular adrenocortical disease (PPNAD), as a rare kind of Cushing's syndrome, is frequently misdiagnosed. To get better understanding of the disease, we analyzed the clinical characteristics and pathogenic variants of PPNAD.Methods: Database was searched, and the pathogenic variants and clinical manifestations of patients were summarized from the relevant articles.Results: Totally 210 patients in eighty-six articles were enrolled with a median age of 22 and femaleto-male ratio of 2:1. Sixty-six (31.43%) patients were combined with Carney complex (CNC) and 94.29% with osteoporosis/osteopenia. Among 151 patients underwent genetic testing, 87.42% (132/151) had pathogenic variants. Six gene mutations (PRKAR1A, PDE11A, PRKACA, CTNNB1, PDE8B, ARMC5) were detected in the patients. The most common mutation was PKAR1A, accounting for 79.47% (120/151). There was a significant correlation between PRKAR1A pathogenic variant and spotty skin pigmentation in CNC concurrent with PPNAD (P<0.05). Among pregnant patients with PPNAD, patient without surgical treatment and with bilateral adrenalectomy suffered high-risk perinatal period. However, patients with unilateral adrenalectomy presented a safe perinatal period.Conclusions: For young Cushing's syndrome patients, especially females with spotty skin pigmentation and osteoporosis/osteopenia, PPNAD should be considered. Unilateral adrenal resection may be considered as an option for women with fertility needs. In view of the difficulty of PPNAD diagnosis, genetic testing before surgery might be a reasonable option. PPNAD patients with spotty skin pigmentation should consider PRKAR1A pathogenic variant and pay attention to CNC.